From the Street Level: Perspectives from Women in Public Administration - Sara R. Rinfret; Eric Wise (Journal of Social Equity and Public Administration, 2025)
Public administration scholars have extensively examined front-line actors within state and local bureaucracies to understand how their daily interactions and perceptions effect policy implementation. This research, however, does not place a focused attention on the gender dynamics at play at the street-level. The purpose of this paper is to offer an alternative way of understanding, listening to the stories and experiences of women at the street-level. Using street-level bureaucracy and emotional labor as descriptive frameworks, qualitative themes are detected from the interviews of 32 women who work for an Arizona state or local agency. The findings from this analysis offer important insights, demonstrating how public sector organizations can begin to hear the experiences of a variety of individuals within our workplaces instead of a few.